Study of clinical symptoms, comorbidities and hospitalization among COVID-19 patients in telemedicine utilizers - Tirupathi, Sushmitha; Balaraju, Ratna; Sandhya, Gunda; Sarma, Mannava Maruti Vara Prasada (International Journal Of Community Medicine And Public Health, 2022)
Background: COVID-19, in those with comorbidities, has an increasingly rapid and severe progression, often leading to death. Telemedicine services provided by the tertiary care centre contributed to decrease the burden of mortality and morbidity patterns by providing the health services during this pandemic. To determine the clinical symptoms in the COVID-19 patients. To estimate the comorbidities in the COVID-19 patients. To find the association between comorbidity and hospitalization among the COVID-19 patients Methods: A descriptive cross-sectional study was conducted among the population who availed for the services of telemedicine. Among the total call data of 9229 a sample of 8638 was obtained. Simple random sampling method used with the help of a pre-designed and pre-tested questionnaire. Data was analyzed using MS excel, SPSS version 19. Results: Demographic profile of the study population of 8638, Males 5862 (67.86%), Females 2776 (32.13%). It shows significant association between symptoms and RTPCR test results. (X2 =12.0 df=1 p=0.0005), Majority of patients presented with comorbidities like diabetes and hypertension and there is significant association between comorbidity and hospitalization. (X2=8.3 df=1 p=0.003) Conclusions: Screening and health education of people with comorbidity regarding clinical symptoms and RTPCR testing of COVID-19 is very crucial for early diagnosis and intervention. Telemedicine services by various NGO’s, Tertiary care hospitals have contributed in providing services with the aim of decreasing the morbidity and mortality due to COVID-19.